Identifying self-regulatory behavior in youth soccer players: A qualitative investigation - Toering, T.; Elferink-Gemser, M. T.; Jordet, G.; Jorna, C.; Visscher, C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Self-regulation refers to processes by which individuals control their thoughts, feelings, and actions (Baumeister & Vohs, 2004). In the learning and development context, it is described as the extent to which individuals are metacognitively, motivationally, and behaviorally proactive in their learning process (Zimmerman, 1986). Talented youth soccer players possess characteristics that facilitate learning, training, and competition (Williams & Reilly, 2000). One of these characteristics may be self-regulation, since self-regulation helps individuals to learn more effectively. Previously, we have measured metacognitive and motivational self-regulation with a questionnaire, and found that elite youth soccer players outscored non-elite players on reflection and effort (Toering et al, 2008). However, we have not yet measured behaviors. If we want to know what these scores mean, thus how much more elite players reflect and invest effort than nonelite players, we have to relate them to overt behaviors (e.g., Andersen et al., 2007; Young & Starkes, 2006). The purpose of this study was to identify self-regulatory behaviors of youth soccer players. Seven expert soccer coaches working with youth soccer players in a talent development program of a Dutch premier league club were interviewed. The interviewer gave definitions of metacognitive and motivational self-regulation, and the coaches were asked to describe behaviors they recognized as self-regulative or non-regulative behaviors during soccer training. Qualitative analysis resulted in a list of self-regulative and non-regulative behaviors, that could be captured in the following themes: focus, time-management, interaction with coach, interaction with team members, resilience, initiative, discipline, and 100% determination to execute tasks. The coaches considered the interaction with coach and team members, discipline, and 100% determination to execute tasks as most important in the development of youth soccer players.